PUZZLE MODALITY THERAPY TO REDUCE DEMENTIA IN THE ELDERLY - Nety Mawarda Hatmanti; Ratna Yunita Sari; Yurike Septianingrum; Difran Nobel Bistara; Choirotussanijjah (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
The condition of the COVID-19 pandemic has changed all arrangements in society, including activities at the Posyandu Lansia. Posyandu Lansia which is held once a week is no longer held considering that the elderly are one of the vulnerable groups. Currently the condition is starting to improve, so it is necessary to do refresher for both cadres and members of the Posyandu Lansia. The purpose of this activity is to increase the knowledge and skills of Posyandu Lansia cadres in providing modality therapy, especially puzzle therapy to reduce the incidence of dementia. The method used in this community service activity is participatory educational approach that is providing health education and demonstrations about puzzle therapy. Furthermore, the Posyandu Lansia cadres apply to the Posyandu Lansia in their area. This activity was carried out for two months and was attended by ten elderly health cadres. Knowledge and skills of cadres in conducting health education about modality therapy was observed by questionnaire. As for the application of puzzle therapy, it was observed using the MMSE (Mini Mental State Examination) questionnaire. The results of community service show that the knowledge and skills of elderly health cadres in implement good health education. The results of puzzle therapy showed that there was a decrease in dementia scores.